2013
DOI: 10.1177/0890334413477240
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Breastfeeding Duration

Abstract: The duration of "exclusive" and "any breastfeeding" was below the Chinese and World Health Organization breastfeeding goals. Shorter duration of breastfeeding was associated with having grandparents residing within the same province, maternal age, illness and employment, gestational age, and delayed onset of lactogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 17 publications
(23 reference statements)
3
40
1
Order By: Relevance
“…Compared to previous studies in China, our study shows a high prevalence of exclusive breastfeeding in the first six months (44.9% vs. 2.6% [11], < 5% [9], 6.2 [23], 28.7% [10], and 35% [8]). The differences between this study and previous reports are likely due to many factors, such as inconsistent operational definitions for exclusive breastfeeding, geographic variations, national and local government efforts, and improved mothers’ awareness of the benefits of breastfeeding.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Compared to previous studies in China, our study shows a high prevalence of exclusive breastfeeding in the first six months (44.9% vs. 2.6% [11], < 5% [9], 6.2 [23], 28.7% [10], and 35% [8]). The differences between this study and previous reports are likely due to many factors, such as inconsistent operational definitions for exclusive breastfeeding, geographic variations, national and local government efforts, and improved mothers’ awareness of the benefits of breastfeeding.…”
Section: Discussioncontrasting
confidence: 83%
“…Previous studies have shown a much lower prevalence of exclusive breastfeeding in infants—35% of infants under 4 months of age were exclusively breastfed in Jinan City, China (2000) [8]; less than 5% infants were exclusively breastfed in the first 6 months of life in Zhejiang province, China (2005) [9]; and 28.7% of infants younger than 6 months of age were exclusively breastfed in twelve central and western provinces (2009) [10]. China initiated the National Basic Public Health Service Program in 2009 to improve essential public health services (including promotion of breastfeeding) in both urban and rural areas [11,12,13]. Only three studies have updated the recent national or local data on the prevalence of breastfeeding.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in Malawi, another qualitative study found that grandmothers felt strongly about the inadequacy of breast milk and reported encouraging mothers to introduce complementary foods early in an infant’s life (Bezner Kerr, et al, 2008). In China, having a grandparent living in the same area as parents (and presumably responsible for caretaking) was associated with shorter duration of breastfeeding in a cohort study (Liu et al, 2013). …”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] Extensive evidence exists to recommend exclusive breastfeeding to 6 months of age, 5 however few mothers reach this goal. 7 Despite positive breastfeeding initiation rates in Australia and other developed countries, many women discontinue breastfeeding in the early postnatal period [8][9][10][11] and recent evidence suggests that only 15.4% of Australian infants are exclusively breastfed up to 6 months of age. 7 Despite positive breastfeeding initiation rates in Australia and other developed countries, many women discontinue breastfeeding in the early postnatal period [8][9][10][11] and recent evidence suggests that only 15.4% of Australian infants are exclusively breastfed up to 6 months of age.…”
Section: Introductionmentioning
confidence: 99%